2002
DOI: 10.1108/09544780210429816
|View full text |Cite
|
Sign up to set email alerts
|

Focusing on key elements of TQM – evaluation for sustainability

Abstract: Without sustainability TQM initiatives are usually doomed to fail. The essence of TQM is continuity over time and integration of quality management initiatives into daily organizational operations. The purpose of this paper is twofold: to define what are the key priority elements of TQM on which companies need to focus and to present an evaluation tool based on these key elements that can be used to assess the extent of progress of TQM. The tool encompasses ISO 9000 as well as TQM elements, bearing in mind tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 21 publications
4
45
0
2
Order By: Relevance
“…As for the advanced techniques, SPC, cost of quality and benchmarking are implemented most in both countries. These results are in accordance with the work by [10]; [7]; and [11].…”
Section: Discussionsupporting
confidence: 95%
“…As for the advanced techniques, SPC, cost of quality and benchmarking are implemented most in both countries. These results are in accordance with the work by [10]; [7]; and [11].…”
Section: Discussionsupporting
confidence: 95%
“…Reed, Lemak, and Mero (2000) pointed out that focusing on sustainability helps gain comparative business advantages. Researchers even stated that without sustainability, TQM initiatives are usually 'doomed to fail' (Curry & Kadasah, 2002). The essence of TQM is continuity over time and integration of quality management initiatives into daily organisational operations.…”
Section: Total Quality Management 39mentioning
confidence: 99%
“…For achieving this, a well-documented quality assurance system is needed to ensure the consistency of the quality related issues in services (Bayraktas et al, 2008). ISO9000 standards, statistical process control (SPC), and qualitative tools and techniques may help to create a solid basis for quality improvement and implementing TQM in an organisation (Curry and Kadasah, 2002;Sila and Ebrahimpour, 2003). Schevermann et al (1997) reported that use of quality tools and techniques in service organisations are suitable and sufficient for its business operations.…”
Section: Quality Systemsmentioning
confidence: 99%